Primary bone graft stability after Latarjet surgery: biomechanical evaluation of a fixation technique with metal-free all-suture cerclage vs. cortical screws - Nolte, Anna-Katharina; Bayer, Tobias; Jäger, Sebastian; Raiss, Patric; Wegmann, Kilian; Kretzer, Jan Philippe; Bülhoff, Matthias; Renkawitz, Tobias; Panzram, Benjamin (Journal of shoulder and elbow surgery, 2024)
Background - To reduce hardware-related complications in coracoid graft fixation to the anterior aspect of the glenoid, a metal-free Latarjet technique was recently introduced. The aim of this study was to compare the primary stability of a classic Latarjet procedure with 2 metal screws to a novel metal-free, all-suture cerclage method. It is hypothesized that fixation of the coracoid graft with 2 malleolar screws will provide higher primary stability compared with an all-suture cerclage technique. - Methods - This biomechanical in vitro study was conducted on 12 fresh-frozen cadaveric shoulders (6 matched pairs) with a mean donor age of 80 years (range, 67-89 years). Coracoid graft fixation was performed using a recently introduced all-suture cerclage technique (group A) or a classic Latarjet technique with two 4.5-mm malleolar screws (group B). The conjoint tendon was loaded with a static force of 10 N to simulate the sling effect. Graft loading with a probe head consisted of 6 ascending load levels (10-50 N, 10-100 N, 10-150 N, 10-200 N, 10-250 N, and 10-300 N) with 100 cycles each at 1 Hz. Relative motion of the bone graft to the glenoid was measured using an optic 3-dimensional system. - Results - While loading the conjoint tendon with 10 N, no difference in mean displacement of the bone-graft was found between both groups (P = .144). During cyclic loading, a significant difference in relative displacement for both groups was already detected in load level 1 (group A: 2398.8 μm vs. group B: 125.7 μm; P = .024), and this trend continued with the following load levels (P < .05). - Discussion and Conclusion - The study demonstrated that the innovative metal-free, all-suture cerclage fixation technique results in higher micromotion than the classic coracoid graft fixation with 2 malleolar screws. According to the present biomechanical investigation, shoulders treated with a metal-free all-suture cerclage technique might need adapted rehabilitation protocols to protect the construct and allow for graft healing.
Online verfügbar: 29. August 2023, Artikelversion: 12. März 2024
Gesehen am 19.09.2024